For this case we must simplify the following expression:
[tex]\frac {\frac {x + 7} {6- (x + 5)}} {x + 3}[/tex]
We must apply double C:
[tex]\frac {(x + 7) (x + 3)} {6- (x + 5)} =[/tex]
We apply distributive property in the numerator:
[tex]\frac {x ^ 2 + 3x + 7x + 21} {6- (x + 5)} =\\\frac {x ^ 2 + 10x + 21} {6- (x + 5)} =[/tex]
In the denominator we have by law of signs:
[tex]- * + = -\\\frac {x ^ 2 + 10x + 21} {6-x-5} =[/tex]
Different signs are subtracted and the sign of the major is placed:
[tex]\frac {x ^ 2 + 10x + 21} {- x + 1}[/tex]
ANswer:
[tex]\frac {x ^ 2 + 10x + 21} {- x + 1}[/tex]